The Role of Strategic Planning and Its Reflection in Sustainable Tourism Development-Karbala Tourism Authority Is An Example (Czech Journal of Multidisciplinary Innovations, 2024)
The study area, which aims to influence strategic planning for sustainable development, is Karbala Provincial Directorate of Tourism. The sample included (30) participants from the employees and employees of the Department of Tourism. Adopting a descriptive analytical approach, a survey was adopted as the main data and information collection tool and Statistician (25) – SPSS was used. Accordingly, a hypothetical model was developed to explain the nature of the relationships and effects between the variables studied. One of the most striking results obtained is the existence of a positive and significant relationship and impact between strategic planning and sustainable tourism development. The most notable recommendations were to work towards greater cooperation and integration of all administrative levels in the strategic planning process within the Ministry of Tourism. The tourism sector is considered one of the vital sectors that contributes to growth and encourages construction. Tourism, which is structural at economic, social, cultural and urban levels, becomes an integrated activity. It covers planning, investment, construction, marketing and promotion and interacts with other sectors. economies of other countries and is therefore considered a contributing factor to the process of economic development. And like every industry Another economic issue is that the tourism sector depends on the resources needed to produce tourism services.We see that most elements of nature and tourism, the most important of which is the environment, are related to image . Direct or indirect damage to natural resource.